The granulocyte colony stimulating factor (G-CSF) activates Jak/STAT and MAPK pathways in a trophoblastic cell line - Marino, Veronica Julieta (2008)
Granulocyte colony-stimulating factor receptor (G-CSFR) has been found in placenta tissues, although its functional role has not yet been defined. In order to explore the molecular pathways induced by G-CSF in this tissue, we first reveal the presence of G-CSFR in the JEG-3 human trophoblastic cell line and then examined the phosphorylation of Janus tyrosine kinases (Jak), signal transducers and activators of transcription (STAT) proteins and mitogen-activated protein kinases (MAPK) after G-CSF binding to receptors. We showed that Jak1, Jak2, Tyk2 and STAT3 were phosphorylated after incubation with G-CSF. Phosphorylation of p38 and p44/42 MAPK was also activated by G-CSF, and specifically blocked in the presence of the corresponding inhibitors. Similar intracellular pathways were induced by G-CSF in a myeloid leukaemia NFS-60 cell line that was studied in parallel. Conversely to cytokine action in myeloid cells, G-CSF did not induce a proliferative response in JEG-3 cells. When the effect of G-CSF on cellular viability was evaluated, cytokine-stimulated JEG-3 cells were protected from foetal serum starvation. In addition, when JEG-3 cells deprived of serum were incubated at different times in the presence of G-CSF, a progressive decrease in the percentage of hypodiploid cells was observed. In summary, we identified the molecular pathways activated after G-CSF binding to trophoblastic cell receptors and showed that G-CSF behaved as a protective cytokine, which supports JEG-3 cells survival.